Sensitivity and Specificity of a COVID-19 Lateral Flow Immunoassay Compared to RT-PCR in Pregnant Womenat Arifin Achmad General Hospital Pekanbaru, Indonesia - Imelda EB Hutagaol; Muhamad Yusuf; NickoPisceski Kusika; Suyanto; Shinta Puja Tilusari (Indian Journal of Forensic Medicine & Toxicology, 2021)
Coronavirus disease 2019 (COVID-19) is significant global treat including to pregnant woman in Indonesia.A point-of-care diagnostic tool that is able to early diagnose and hasa good sensitivity and specificity iscritical during the pandemic. The aim of this study was to describe the clinical, laboratory and outcomesof pregnant women with presumptive COVID-19 and to compare the sensitivity and specificity betweenCOVID-19 rapid test (lateral flow immunoassay) and real-time reverse transcription polymerase chainreaction (RT-PCR). Pregnant women with presumptive COVID-19 symptoms were recruited at ArifinAchmad General Hospital between April 2020 and December 2020. Demographic and clinical data werecollected and patients were tested with COVID-19 rapid test as well as RT-PCR. Analyze was conducted todetermine the sensitivity and specificity. We included 120 patients with presumptive COVID-19 of which48 (40%) and 72 (60%) of patients were reactive for IgM and IgG antibody anti severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2), respectively and 51 (42.5%) were reactive for both IgM and IgG.The sensitivity and the specificity of rapid test was 64.0% and 33.3%, respectively. The positive and negativepredictive value was 61.5% and 35.7%, respectively. In conclusion, lateral flow immunoassay-based rapidtest has relatively low sensitivity and specificity in diagnosing COVID-19 in pregnant women.